Perbedaan Hasil Belajar Penjumlahan dan Pengurangan Dua Pecahan dengan Penyebut Berbeda Menggunakan Model Kooperatif Tipe STAD dan TAI di Kelas V SD Kenagarian Dalko Kabupaten Agam - Yanti, Mirna; Zen, Mulyani; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of the research is to know differences about student’s achievement in addition and subtraction of two fractions with different denominators by using cooperative model with STAD and TAI types. The design of the research is quasi experiment in the from pretest-posttest non-equivalent group. The sample of the research is class VA  andclass VB at Elementary School 38 Lubuk Sao that have chosen by using purposive sampling technique. The result of research found that there is differences about student’s achievement in learning mathematic by using cooperative model STAD type and cooperative model TAI type tcount (1,80664)>ttable (1,69726). This means that students’ achievement by using cooperative model STAD type better than students’ achievement by using cooperatuve model TAI type in learning mathematics. Keywords: cooperative model STAD type, cooperative model TAI type, addition and substraction of two fractions with different denominators.Daryanto. 2012. Model Pembelajaran Inovatif. Yogyakarta: Gava Media. Fathurrohman, M. 2015. Model-model Pembelajaran Inovatif. Yogyakarta: Ar-Ruzz Media. Harsanti, Arni Gemilang. 2017. “Perbandingan Model Pembelajaran STAD dengan Model TAI (Team Assisted Individualization) Terhadap Hasil Belajar Matematika Siswa Kelas V Sekolah Dasar”. Jurnal Pendidikan Dasar (Volume 4 Edisi 1). Hlm. 12-18. Heruman. 2013. Model Pembelajaran Matematika di Sekolah Dasar. Bandung: PT. Remaja Rosdakarya. Huda, Miftahul. 2013. Model-Model Pengajaran dan Pembelajaran. Yogyakarta: Pustaka Pelajar. Ngalimun, dkk. 2015. Strategi dan Model Pembelajaran. Yogyakarta: Aswaja Pressindo. Nugroho, Oky Wasrik Dwi. 2014.”Pengaruh Penerapam Model Pembelajaran Kooperatif Tipe STAD Terhadap Peningkatan Prestasi Belajar Mata Pelajaran IPS Pada Siswa Kelas IV SD N Karang Duren”.Skripsi. Yogyakarta: UNY.Purnami, Agustina Sri dan Nurhayati. 2016. “Studi Komparasi Pembelajaran Student Team Achievement Divisions dan Team Accelerated Instruction Terhadap Hasil Prestasi Belajar dan Minat Belajar Matematika Siswa Kelas VII SMP Muhammadiyah 1 Wonosari”. Jurnal Pendidikan Matematika (Volume 4 Edisi 1). Hlm. 125-132. Purwanto, Ngalim. 2006. Prinsip-Prinsip dan Teknik Evaluasi Pengajaran. Bandung: PT Remaja Rosda Karya. Ruseffendi. 2006. Pengantar Kepada Membantu Guru Mengembangkan Kompetensinya dalam Pengajaran Matematika Untuk Meningkatkan CBSA. Bandung: Tarsito. Rusman. 2011. Model-Model Pembelajaran. Jakarta: Rajawali Pers.